The myth of research-based policy & practice - Hammersley, Martyn (Los Angeles : SAGE, 2016)
Structured as a series of probing questions, and covering a range of methods, this book reflects on the challenge posed by the idea that social research should serve evidence-based practice.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 13, 2016).
Keywords: elektronické knihy; electronic books; Social sciences -- Research